Remote Auditing Processes in The Context of Global Pandemic Times: A Case of Food Processing Manufacturers in Poland - Pawel NOWICKI (Communications of International Proceedings, 2021)
Research background: Conformity assessment as defined in the ISO/IEC 17000 standard shows that the specified requirements for the product, process, system, person or entity have been met. A special type of conformity assessment is certification, in which the assessment is carried out by independent organizations, which has been confirmed by an accreditation body. The current crisis related to the development of the COVID-19 global pandemic has forced many organizations to change traditional forms of operation and, where it was possible, switch to a remote mode of work within auditing processes. Purpose of the article: The need to adapt to the new realities has not bypassed the certification bodies and food producers, which had to adapt to the emergency situation, using the possibilities of remote work, including remote audits as part of certification processes. The purpose of this publication is to indicate the context of the operation of both certification bodies as well as food producers in relation to the remote auditing and certification process and the impact of such proceedings on the confidence in the results of their work, and to indicate changes in the way certification audits are carried out by certification bodies. Methods:  For above mentioned matter, food processing manufacturers operating on a polish market were surveyed in remote auditing processes carried out by certification bodies. The used methodology was a survey carried out during COVID-19 pandemic lockdown in Poland in the year of 2020. Findings and Value Added: The main findings are related to the following issues concerning that remote auditing processes ensure business continuity; the effectiveness of remote audits is generally comparable to the on-site once; there is an increased confidence in results among customers of certification bodies;  the expected decrease in prices of the remote assessment and certification process is not yet clearly visible, although it can be observed; the companies that undergone the remote audits more likely choose this kind of assessment again.
Keywords: Remote Auditing; Global Pandemic; Standardized Management Systems; Food Production.